Developmental changes in resting‐state functional networks among individuals with and without internalizing psychopathologies. Issue 2 (5th December 2018) - Burkhouse, Katie L.; Stange, Jonathan P.; Jacobs, Rachel H.; Bhaumik, Runa; Bessette, Katie L.; Peters, Amy T.; Crane, Natania A.; Kreutzer, Kayla A.; Fitzgerald, Kate; Monk, Christopher S.; Welsh, Robert C.; Phan, K. Luan; et al.
Abstract : Background: Three well‐established intrinsic connectivity networks (ICNs) involved in cognitive‐affective processing include the cognitive control network (CCN), default mode network (DMN), and salience and emotional network (SEN). Despite recent advances in understanding developmental changes in these ICNs, the majority of research has focused on single seeds or networks in isolation with limited age ranges. Additionally, although internalizing psychopathologies (IPs), such as anxiety and depression, are often characterized by maladaptive cognitive‐affective processing styles, it is not clear how IP history influences age‐related changes in brain networks. Method: The current study aimed to characterize the normative development of the CCN, DMN, and SEN across a large age‐span (7–29 year olds) of typically developing (TD) individuals ( n = 97). We also explore how age may impact differences in network connectivity between TD individuals and patients with IPs ( n = 136). Results: Among TD individuals, DMN and CCN connectivity strengthened with age, whereas connectivity between the SEN and ventromedial prefrontal cortex weakened across development. When exploring group (IP vs. TD) differences, the IP group was characterized by greater connectivity between the CCN and cerebellum and between the SEN and caudate from childhood to early adulthood, relative to TD individuals. In addition, patients with IPs, versus TD individuals, exhibited reduced connectivity between the SEN and medial frontal gyrus from adolescence to adulthood. Conclusions: The current findings shed light on differential age‐related changes in brain network patterns among psychiatrically free, TD individuals and those with internalizing disorders, and may provide plausible targets for novel mechanism‐based treatments that differ based on developmental stage.